The Hubungan Indeks Gizi Seimbang Dengan Status Gizi Pada Remaja Putri Di SMK Kota Bekasi - Fristy Rahmazahra Danty; Muhammad Nur Hasan Syah; Afrinia Eka Sari (HB PRESS, 2019)
Healthy Eating Index was known as Indeks Gizi Seimbang in Indonesia. Healthy Eating Index is a measure of the suitability of subject consumption to the recommended meal portion from the Balanced Nutrition Guidelines. If the subject IGS score approaches the maximum number, this indicates a good quality of the subject food consumption and in accordance with the recommended Balanced Nutrition Guidelines. This study was aimed to determine the relationship of balanced nutritional index with nutritional status at adolescent women in SMK Kota Bekasi. This study was an observational analytic study by cross sectional design. The subject of this study was women adolescent with the age between 14-18 years old. This study was located in SMKN 2 Kota Bekasi, SMKN 3 Kota Bekasi, SMKN 5 Kota Bekasi, SMKS Bina Karya Mandiri, and SMKS Bina Husada Mandiri. Data collected by interview using FFQ (Food Frequency Questionnaire) then examined by chi square test. The percentage of food consumption quality with the bad category was 55% and with the very good category was only 6%. The conclusion of this study is there is no relationship between healthy eating index with the nutritional status of women adolescent. But there is a relationship between healthy eating index of the vegetables component with the nutritional status of women adolescent.